Academisation of Schools in England and Placements of Pupils With Special Educational Needs: An Analysis of Trends, 2011–2017 - Black, Alison; Bessudnov, Alexey; Liu, Yi; Norwich, Brahm (Frontiers in Education, 2019)
This paper aims to examine the changes in school composition in England from 2011 to 2017 by school type and school phase; the speed of academisation by region; and the changes in the proportions of pupils with special educational needs (SEN) at SEN Support and EHC Plan levels overall. We analyse publicly available school level data from the National Pupil Database (NPD) to document two simultaneous trends in English education between 2011 and 2017. First, we observe an increasing percentage of the schools that have become Academies, especially in the secondary mainstream sector, but also among primary schools, special schools and pupil referral units. Second, we document a decreasing percentage of pupils who were classified as having SEN. While the decrease happened across all types of schools, it was particularly steep in Sponsored Academies. This evidence does not necessarily imply that the academisation of English schools has had a negative effect on the inclusion of pupils with SEN. However, the findings have significance to provide the basis for a more in-depth analysis of these trends and the causal effects of academisation involving individual and school level analyses. They can also inform national and local policy review of how pupils are identified as having SEN and in the context of international moves towards greater inclusive education.